Hemifacial spasm caused by unruptured fusiform vertebral aneurysm treated with endovascular coil embolization: a case report - He, Pengchen; Li, Zongping; Jiang, Han (Frontiers in Neurology, 2023)
Hemifacial spasm due to fusiform aneurysm of vertebral artery is extremely rare. lateral spread response (LSR) is routinely used to monitor hemifacial spasm during microvascular decompression to predict the degree of postoperative remission of hemifacial spasm. We report a case of hemifacial spasm caused by an unruptured fusiform vertebral aneurysm treated with intravascular intervention and monitoring of LSR. A 59-year-old man was admitted to the hospital with left facial spasm that gradually worsened for 1 year. Preoperative cerebrovascular angiography indicated fusiform aneurysms in the intracranial segment of the left vertebral artery, close to the left facial nerve. The patient underwent parent artery occlusion and aneurysm embolization, and LSR was monitored intraoperatively. After intraoperative aneurysm embolization, LSR disappeared immediately. Postoperative review of cerebrovascular angiography indicated that the parent artery and aneurysm were embolized successfully, and the patient's left facial spasm was relieved after surgery. Hemifacial spasm caused by vertebral artery fusiform aneurysm can be safely and effectively treated by parent artery occlusion and aneurysm embolization. Meanwhile, intraoperative LSR monitoring can be used to predict postoperative efficacy.